Impact of virtual reality use on the teaching and learning of vectors - Campos, Esmeralda; Hidrogo, Irving; Zavala, Genaro (Frontiers in Education, 2022)
The use of virtual reality in education has enabled the possibility of representing abstract concepts and virtually manipulating them, providing a suitable platform for understanding mathematical concepts and their relation with the physical world. In this contribution, we present a study that aims to evaluate the students’ experience using a virtual reality (VR) tool and their learning of three-dimensional vectors in an introductory physics university course. We followed an experimental research design, with a control and an experimental group, for measuring students’ performance in a pre-post 3D vectors questionnaire. We surveyed the experimental group about their perception of VR use regarding their learning objectives, their experience using VR as a learning tool during the sessions, and the value of using VR in class. We found that on the items in which visualization was important, students in the experimental group outperformed the students in the control group. Students evaluated the VR tool as having a positive impact on their course contents learning and as a valuable tool to enhance their learning experience. We identified four hierarchical categories in which students perceived the use of virtual reality helped them learn the course contents: Visualization, 3D Visualization, Identification, and Understanding. Overall, this study’s findings contribute to the knowledge of using virtual reality for education at the university level. We encourage university instructors to think about incorporating VR in their classes.